2003
DOI: 10.2527/2003.81112792x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding a blend of grains naturally contaminated with Fusarium mycotoxins on growth and immunological measurements of starter pigs, and the efficacy of a polymeric glucomannan mycotoxin adsorbent1

Abstract: An experiment was conducted to investigate the effects of feeding a blend of grains naturally contaminated with Fusarium mycotoxins on growth and immunological parameters of starter pigs. A polymeric glucomannan mycotoxin adsorbent (GM polymer, Alltech Inc., Nicholasville, KY) was also tested for its efficacy in preventing Fusarium mycotoxicoses. A total of 150 starter pigs (initial weight of 9.3 +/- 1.1 kg) were fed one of five treatment diets (six pens of five pigs per diet) for 21 d. Diets included control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
64
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 24 publications
10
64
3
Order By: Relevance
“…Pigs on MYCO were given a diet containing 5% naturally contaminated wheat. The diet contained a mixture of (mg/kg diet) deoxynivalenol (5.8), fusaric acid (49.3), zearalenone (0.5) and 15-acetyldeoxynivalenol (0.3), as described previously by Swamy et al (2003). Pigs were randomly assigned to the three treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Pigs on MYCO were given a diet containing 5% naturally contaminated wheat. The diet contained a mixture of (mg/kg diet) deoxynivalenol (5.8), fusaric acid (49.3), zearalenone (0.5) and 15-acetyldeoxynivalenol (0.3), as described previously by Swamy et al (2003). Pigs were randomly assigned to the three treatments.…”
Section: Methodsmentioning
confidence: 99%
“…The studies performed with EG (0.5 and 1 g/kg) at different concentrations of AF (0.05 to 5 mg/kg) in broilers (Raju and Devegowda, 2000;Aravind et al, 2003;Santin et al, 2003) showed that EG partially and/or completely reversed the adverse effect of AF on performance, biochemistryhaematology and immune responses of birds. EG was also used for detoxification of other mycotoxins such as zearalenone (Swamy et al, 2003) and aurofusarin (Dvorska and Surai, 2001).…”
mentioning
confidence: 99%
“…Deoxynivalenol (DON) content was analysed using high performance liquid chromatography (HPLC) as presented by Swamy et al (2003). The limits of detection were 0.10 ppm for ZEA and DON and 0.25 ppm for FUM.…”
Section: Analysis Of Mycotoxinsmentioning
confidence: 99%